Pembelajaran Pendidikan Multikulturalisme Berbasis Sejarah Lokal Cirebon-Indramayu - SYUKRON MA’MUN; Eva Nur AROVAH (UIN Fatmawati Sukarno Bengkulu, 2024)
This research is the result of an analysis of the multiculturalism values of Cirebon-Indramayu as a historical reality that cannot be denied by anyone. The taking of spatial boundaries by selecting two regions (Cirebon and Indramayu) is based solely on the consideration that in the course of its history, administratively the Indramayu region was once part of the territory of the Islamic Kingdom of Cirebon and Karesidenan Cirebon. This reason is then used as a reference in selecting the research location. To facilitate the description of Cirebon-Indramayu history and the phenomenon of multiculturalism in it, the author use four historical research steps including heuristics, criticism, interpretation, and historiography. After the historical facts that show aspects of multiculturalism in Cirebon-Indramayu are obtained, the next step is how the message of multiculturalism obtained can be presented in the lecture room in learning local history courses. For this reason, this research will also be continued with the application of the Reflective Pedagogical Paradigm (PPR) approach as a learning effort that integrates the history of Cirebon-Indramayu with the values of multiculturalism. As a result, the Cirebon-Indramayu history study, which was adjusted to the context of the student, students understand the history of their area and the values of multiculturalism were able to be confirmed through the dynamics of experience, reflection, and action. Ultimately, Bhineka Tunggal Ika is not just a slogan that is echoed everywhere, but it is true. The affirmation of the value of multiculturalism in the history of Cirebon-Indramayu is also an attempt to place the value of multiculturalism in the history of Cirebon-Indramayu in line with historical facts that have become the narrative and object of previous historical research.